Representation of Women Power in Beyoncé Knowless’ song “Run The World (Girls)” - Neni Kurniawati (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2021)
Song is one of the propaganda media for ideolgy. Beyonce Knowless's song “Run the World (girls)” is an example of a song that raises the issue of Black Feminism Thought. This paper will discuss how textual and discursive practices through the signs in the text of the song lyrics and video clips of the song in constructing the paradigm of black women power or black feminism thought. By interpreting the structure of the text in the lyrics of the song and the visual signs in the video clip of the song "Run the World (girls)" to find meaning and ideology reproduced in the song. The results show that the dialectic of verbal and visual signs represents black women power and to bolster black women to become well-respected women especially by black men. The presence of this song is also related to the black feminist movement which propagates their ideology through song media. The independence of black women in the economic and educational aspectss, as well as the ability to bare children are discourses that are reproduced by the singer to make social changes in black women’s live.Keywords: Black woman, discourse, hermeneutics, ideology, Paul Ricouer